2018
DOI: 10.1111/risa.12985
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Fish and Shrimp from Southeast Louisiana Poses No Unacceptable Lifetime Cancer Risks Attributable to High‐Priority Polycyclic Aromatic Hydrocarbons

Abstract: Following oil spills such as the Deepwater Horizon accident (DWH), contamination of seafood resources and possible increased health risks attributable to consumption of seafood in spill areas are major concerns. In this study, locally harvested finfish and shrimp were collected from research participants in southeast Louisiana and analyzed for polycyclic aromatic hydrocarbons (PAHs). PAHs are some of the most important chemicals of concern regarding oil-spill-contaminated seafood resources during and following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
(80 reference statements)
1
15
0
Order By: Relevance
“…In a study conducted 1.5 years [ 13 ] after the spill, the oxidative DNA stress marker levels, which could be indicative of cancer risk, were higher in the high-exposure group than in the low-exposure group; the effect persisted for 6 years after the spill [ 14 ]. Chromosome damage was observed among fishermen in studies conducted two and six years after the Prestige oil spill in Spain [ 15 , 16 , 17 ], and cancer risk modeling was performed after the British Petroleum Deepwater Horizon (BPDH) oil spill in the United States of America (USA) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted 1.5 years [ 13 ] after the spill, the oxidative DNA stress marker levels, which could be indicative of cancer risk, were higher in the high-exposure group than in the low-exposure group; the effect persisted for 6 years after the spill [ 14 ]. Chromosome damage was observed among fishermen in studies conducted two and six years after the Prestige oil spill in Spain [ 15 , 16 , 17 ], and cancer risk modeling was performed after the British Petroleum Deepwater Horizon (BPDH) oil spill in the United States of America (USA) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…While oil spills have occurred across the world, studies on the associated mid- and long-term health effects have been reported only in three countries: Spain (Prestige oil spill), the USA (Exxon Valdez oil spill [ 19 , 20 , 21 ] and the BPDH oil spill [ 18 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]), and Korea (HSOS) [ 2 , 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. There have been concerns pertaining to the potential development of cancers in the affected areas; however, few studies have focused on the cancer incidence among residents after the oil spill despite their consequent exposure to carcinogenic substances.…”
Section: Introductionmentioning
confidence: 99%
“…Table S4 (supplementary data) summarizes published studies from 2004-2020 regarding shrimp contamination with PAHs [ 24 , 25 , 36 , 52 , 54 , 60 , 69 , 71 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 ]. As demonstrated in Table S4 the 16 PAHs that EPA listed as priority pollutants are the most studied ones.…”
Section: Occurrence Of Pollutants In Shrimpsmentioning
confidence: 99%
“…The most applied sample catchment method was trawl fishing [ 24 , 113 , 116 , 118 ] and one author reported the use of a scoop net [ 71 ]. As possible pollution sources of PAHs near the sampling locations the authors indicated highly urbanized and industrialized areas [ 54 , 60 , 71 , 110 , 117 , 118 ], more specifically industry, such as petrochemical refineries, nuclear power stations and thermal power stations [ 24 , 106 , 109 , 113 ], oil spills [ 105 , 112 , 115 , 120 ], and specifically the deepwater horizon oil spill [ 36 , 114 , 116 ], another possible source of PAHs formation can be the grilling of food [ 108 , 111 ].
Figure 4 Reported concentrations of Ʃ16 priority PAHs found in shrimp samples, from 2004 to 2020.
…”
Section: Occurrence Of Pollutants In Shrimpsmentioning
confidence: 99%
“…CS projects resulted in new plant varieties for organic farming (Lyon et al 2018); greater understanding of pollinator health (Bloom and Crowder 2020); evidence of linkage between antibiotic-resistant bacteria and livestock worker health (Guidry et al 2018;Hatcher et al 2017aHatcher et al , 2017bNadimpalli et al 2015Nadimpalli et al , 2016Rhodes et al 2020;Rinsky et al 2013); and documentation of pesticide drift into homes and schools (Harrison 2011(Harrison , 2017Marquez and Schafer 2017). Some projects directly helped community members to document contamination from oil sands development (Baker 2016;Baker and Fort Mackay Berry Group 2019) and from an oil spill (Simon-Friedt et al 2016;Wickliffe et al 2018;Wilson et al 2015). CS also provided data that enabled citizens to avoid environmental and health harms, such as reducing exposure to heavy metals found in garden soil and collected rainwater (Ramirez-Andreotta et al 2013, 2014, 2015Sandhaus et al 2018;Soleri et al 2016).…”
Section: Introductionmentioning
confidence: 99%